Deconstructing the Carter Review: competing conceptions of quality in England's 'school-led' system of initial teacher education. Issue 1 (2nd January 2017) - Mutton, Trevor; Burn, Katharine; Menter, Ian
Abstract: The commitment to establish a 'school-led' system of teacher education in England, announced by the Coalition Government in 2011 and relentlessly pursued thereafter, represented a radical departure from previous kinds of initial teacher education partnership. While it is entirely consistent with a neoliberal agenda, with its strong regulatory framework and appeal to market mechanisms, it is also underpinned by a particular conception of teaching as a craft – 'best learnt as an apprentice observing a master craftsman or woman'. In 2014, the government established a Review of Initial Teacher Training, led by a primary school head teacher, Sir Andrew Carter. This signalled the recognition of teacher education as a 'policy problem', adopting Cochran-Smith's term. The ensuing report, published in early 2015, was more nuanced than might have been anticipated, although a number of profound tensions emerge from a closer analytical reading; four of these tensions are similar to those previously defined by Cochran-Smith and two are newly emergent. This paper identifies and discusses these tensions as they appear in the Carter Review and relates them to wider debates about the links between teaching, teacher education, evidence and research and to policy-making processes in education.